Some Observations on the Learning of Economics - Boulding, Kenneth E. (American Economic Review, 1975)
We probably pay too much attention to the teaching of economics and not enough to the learning of it, that is, to those processes of reorganization in the structure or image which result from being exposed to the body of public knowledge which economists share. All learning processes involve the reconstruction of images. This sometimes involves fairly drastic reorganization change in existing images; sometimes it merely involves addition to the existing structure. Thus, when we learn that Sacramento is the capital of California, this simply adds to our geographical knowledge of the United States without any very fundamental change in the structure. When we learn, however, that the shortest way from California to Iran is over the North Pole, if we have previously structured our world on Mercator's Projection, this is quite a shock and will create a considerable reorganization of our geographical image. The learning process, therefore, depends a great deal on where people start from, that is, what images of the system they have in their minds at the beginning of the process; and it depends also on the creation of certain shocks or inconsistencies, what Leon Festinger has called cognitive dissonances, which force a reorganization of the structure of these initial images. In discussing the teaching of economics, we have usually been singularly insensitive to the problem of what images of the economic system people start with. If we don't know what it is we are modifying, we may not be successful in modifying it. In a sense the object of formal education is to move images in the minds of the students from private and idiosyncratic images toward publicly held images. This is not to say that the public image is always right. Indeed, change in the public image always arises because some private, idiosyncratic image fails to correspond to it, although it corresponds more to the truth. Nevertheless, for most purposes we assume that the teacher's image is right and that the student's initial image is wrong and that the business of education is to change the image in the mind of the student in the direction of the image in the mind of the teacher. If we look at the learning process in this way, it might occasion a certain change in our methods of teaching. The traditional method is to create a large flood of information input into the student's ear, and perhaps into his eye, in the hope that this input will create a change in the student's image in the direction of that held by the teacher. Most of the feedback to the teacher, however, comes from his own internal perceptions as to whether the information stream which he is emitting is consonant with the image which he holds. * University of Colorado.